How effective are integration policy reforms? The case of asylum‐related migrants. (27th January 2022) - Pecoraro, Marco; Manatschal, Anita; Green, Eva G. T.; Wanner, Philippe
Abstract: The marked increase of asylum seekers arriving in Western Europe after 2014 has renewed debates on policy measures that countries should put into place to support their integration. Although implemented by many countries in recent years, research has neglected the effect of integration policy reform packages combining economic and social policy measures on asylum‐related immigrants' adjustment processes. Exploiting a comprehensive integration policy reform in Switzerland, using survey data from the Health Monitoring of the Swiss Migrant Population, and registering data on the whole asylum‐related population, our difference‐in‐differences analyses reveal that provisionally admitted individuals benefiting from the reform have higher employment probability, increased income levels, better language skills, and feel less lonely or without a homeland relative to comparable asylum seekers who did not benefit from the reform. Robustness checks assessing common pre‐reform trends support our findings, which highlight the importance of evaluating entire reform packages when assessing integration policies' effectiveness.